Leaving no hole unclosed: left atrial appendage occlusion in patients having closure of patent foramen ovale or atrial septal defect - Gafoor, Sameer; Franke, Jennifer; Boehm, Patrick; Lam, Simon; Bertog, Stefan; Vaskelyte, Laura; Hofmann, Ilona; Sievert, Horst (Journal of interventional cardiology, 2014)
Objectives To report procedural outcome of sequential occlusion of the left atrial appendage (LAA) and an interatrial septal communication and discuss possible indications. Background There are some patients who may have indications for both closure of patent foramen ovale (PFO) or atrial septal defect (ASD), as well as closure of the LAA. The optimal procedural strategy is not known. Methods A retrospective review of LAA and PFO/ASD cases at our center was performed. Demographic, echocardiographic, and procedural data were recorded. Results Closure of LAA and then PFO/ASD (Group I: 11 patients), closure of both in the same setting (Group II: 3 patients), and closure of the PFO/ASD and then the LAA (Group III: 3 patients) was performed in a total of 17 patients. Average age was 63.5 ± 9.8 years. Most patients were hypertensive with prior cerebrovascular event in 52.9% of patients. Procedural success was 100%. Procedural adverse events were 2 episodes of tamponade (in Group I after first LAA procedure) treated with pericardiocentesis and 1 access-site hematoma (Group II) treated conservatively. Conclusions Sequential (staged or during the same procedure) closure of the LAA and interatrial communications can be performed safely in a carefully selected patient population. This is also the first known report of LAA occlusion in patients with prior septal closure devices. (J Interven Cardiol 2014;27:414-422)
Gesehen am 04.09.2020